The value of x is equal to -6.
The value of y is equal to 3.
8x + 2y = -42
4x + 7y = -3
In the first equation, subtract 8x from both sides.
2y = -42 - 8x
Divide all terms by 2.
y = -21 - 4x
Now that we have a value of y, we can plug it into the second equation to solve for x.
4x + 7(-21 - 4x) = -3
Distributive property.
4x - 147 - 28x = -3
Combine like terms.
-24x - 147 = -3
Add 147 to both sides.
-24x = 144
Divide both sides by -24.
x = -6
Now that we have a true value for x, we can plug it into either equation to solve for y.
8(-6) + 2y = -42
-48 + 2y = -42
Add 48 to both sides.
2y = 6
Divide both sides by 2.
y = 3